Peptide-conjugated nanoparticles for targeted imaging and therapy of prostate cancer. (August 2016) - Yeh, Chen-Yun; Hsiao, Jong-Kai; Wang, Yi-Ping; Lan, Chun-Hsin; Wu, Han-Chung
Abstract: While there has been extensive development of anti-cancer drugs for treatment of prostate cancer, the therapeutic efficacy of such drugs remains inadequate in many cases. Here, we performed in vitro biopanning of the PC3 human prostate carcinoma cell line to select prostate cancer-specific peptides by phage display. We successfully identified specific peptides targeting prostate cancer cells, and their specificity was confirmed by cellular ELISA and flow cytometry. Moreover, we found that the phage clones also recognize other prostate cancer cell lines and surgical specimens from prostate cancer patients. The tumor targeting ability of these phages was validated in a xenograft model, in which high accumulation of targeting phage was observed. To investigate whether selected peptides are able to target tumors and enhance drug delivery into cancer cells, we synthesized peptide-PEGylated lipids and post-inserted them into preformed liposomal doxorubicin and vinorelbine. The results of our cellular uptake and MTT assays indicate that peptide-conjugated liposomes exhibit enhanced drug intracellular delivery and cytotoxicity. The conjugation of targeting peptide to imaging agents, such as quantum dots (QDs) and superparamagnetic iron oxide nanoparticles (SPIONs), results in more precise delivery of these agents to tumor sites. Furthermore, administration of liposomal doxorubicin and vinorelbine conjugated with targeting peptides was found to markedly increase the inhibition of human prostate tumor growth in mouse xenograft and orthotopic models. These results indicate that targeting peptide, SP204, has significant potential for targeted therapy and molecular imaging in prostate cancer.